RECOGNITION OF TRADITIONAL INHERITANCE LAW IN INDONESIA: A CASE STUDY OF SEDULUR SIKEP TRADITIONAL SOCIETY - B. Rini Heryant; Amri Panahatan Sihotang; Aga Natalis (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The system of traditional inheritance law in Indonesia often comes into conflict especially with the inheritance law system in the Burgerlijk Wetboek and the Islamic law system, which in many cases often has problems between those three law systems. This study aims to determine and analyze the pluralism of inheritance law in Indonesia and the recognition model of law for traditional inheritance law and the inheritance law system in the sedulur sikep traditional community. This research uses a qualitative method with a normative juridical approach and descriptive-analytical research specification. The results show that the pluralism of inheritance law in Indonesia and the recognition model for traditional inheritance law, that there is an inheritance law system, namely the civil law inheritance system or Burgerlijk Wetboek, the Islamic inheritance law system, and the traditional inheritance law system. Recognition of the traditional inheritance law system based on Pancasila and Article 18B Paragraph (2) of the 1945 Constitution of the Republic of Indonesia. The inheritance law system in the Sedulur Sikep traditional community, that the inheritance is divided into each asset that has been divided into individual property rights, and each individual can receive it properly without jealousy